Intravitreal tissue plasminogen activator in the management of central retinal vein occlusion - Ghazi, Nicola (2003)
Purpose To evaluate the role of intravitreal tissue plasminogen activator (tPA) in the management of central retinal vein occlusion (CRVO) in patients with symptoms for <3 days. Methods We evaluated the visual outcome of a consecutive series of patients with CRVO following intravitreal tPA injection. All patients presented with visual acuity worse than 20/50 within 3 days from the onset of symptoms. Main outcome measures included percentage of patients whose final vision improved to 20/50 or better and change in percentage of patients with vision of 20/200 or worse before and after treatment. Results Twelve patients received intravitreal tPA for CRVO. Nine patients (75%) had best-corrected visual acuity of 20/200 or worse at presentation compared with 4 patients (33%) at the last follow-up after treatment. Five (55%) of these 9 patients had final visual acuity that improved to 20/50 or better. The remaining four patients did not have improvement or their vision continued to worsen. All 4 patients had fluorescein angiographic evidence of >10 disk areas of capillary nonperfusion at presentation. Overall, 8 (67%) of 12 patients had final visual acuity of 20/50 or better. No side effects related to tPA injection were observed. Conclusion Our data suggest that intravitreal tPA injection may have a beneficial role in the management of CRVO when used within a few days of the onset of symptoms in patients with no angiographic evidence of severe capillary nonperfusion even if initial visual acuity is 20/200 or worse.